Disrupted RabGAP Function of the p85 Subunit of Phosphatidylinositol 3-Kinase Results in Cell Transformation - Chamberlain, M. Dean (American Society for Biochemistry and Molecular Biology, 2008)
Rab proteins regulate vesicle fusion events during the endocytosis, recycling, and degradation of activated receptor tyrosine kinases. The p85α subunit of phosphatidylinositol 3-kinase has GTPase-activating protein activity toward Rab5 and Rab4, an activity severely reduced by a single point mutation (p85-R274A). Expression of p85-R274A resulted in increased platelet-derived growth factor receptor (PDGFR) activation and downstream signaling (Akt and MAPK) and in decreased PDGFR degradation. We now report that the biological consequences of p85-R274A expression cause cellular transformation as determined by the following: aberrant morphological phenotype, loss of contact inhibition, growth in soft agar, and tumor formation in nude mice. Immunohistochemistry shows that the tumors contain activated PDGFR and high levels of activated Akt. Coexpression of a dominant negative Rab5-S34N mutant attenuated these transformed properties. Our results demonstrate that disruption of the RabGAP function of p85α due to a single point mutation (R274A) is sufficient to cause cellular transformation via a phosphatidylinositol 3-kinase-independent mechanism partially reversed by Rab5-S34N expression. This critical new role for p85 in the regulation of Rab function suggests a novel role for p85 in controlling receptor signaling and trafficking through its effects on Rab GTPases.